Between Nations or Cultures: Dilemmas Related to Intellectual Property Based on Traditional Cultural Expression from a Legal Philosophy Perspective - Dita Perwitasari; Budi Santoso; Yunanto; Puja Aqdamuyasrro; Cantika Sari Siregar (Universitas Negeri Surabaya, 2025)
The expression of traditional cultural expressions as intellectual property is the result of the community's collective creativity and intellectuality and must receive effective legal protection. In practice, there is often a phenomenon of filtering claims between countries regarding the existence of a particular cultural expression. This research is normative legal research that emphasizes philosophical, conceptual, and legislative approaches. The research findings confirm that the state plays a role in promoting respect for and recognition of traditional cultural expressions as intellectual property, serving as a collective human identity through policy, education, and public awareness programs. From a legal philosophical perspective, the recognition of traditional cultural expressions faces dilemmas and conflicts, primarily due to the communal nature and cross-border existence of such cultures. Therefore, an update to international regulations is needed, particularly the Convention on the Safeguarding of the Intangible Cultural Heritage (CSICH), which must affirm the communal nature of such intellectual property and regulate fair and pluralistic mechanisms for resolving disputes between countries. The main recommendation is to revise the CSICH to accommodate communal characteristics and clarify mechanisms for resolving disputes over cultural recognition between countries.